Preparation and characterization of alumina loaded titania in the photoreduction of CO2 - Norhaszjana, Awang Hasan (2012)
Nowadays, the atmospheric concentration of carbon dioxide (CO2) had been increased due to the globalization and technology created by human activities. CO2 is one of the major contributors to greenhouse effects which will leads to global warming. Therefore alternative routes should be taken to overcome this problem. One of the best remediation is to transform CO2 into useful hydrocarbon by using photoreduction. Photoreduction is one of the methods which can be used to reduce the concentration of CO2 released to the atmosphere. The aim of this study was to find a new catalyst produced with the best method in photoreduction process. Catalyst plays an important role to accomplish specific tasks with greater efficiency and speed. The metal oxides, Alumina (Al2O3) was chosen to be use in this research which was loaded with Titania (TiO2). Al2O3-TiO2 catalyst was prepared by using two different methods which are sol gel and hydrothermal method. The prepared catalysts were analyzed and characterized by using Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectroscopy (FTIR), X-Ray diffraction (XRD) and Brunauer-Emmett-Teller (BET) method. Experimental results demonstrated that hydrothermal method was a promising technique for preparing Al2O3-TiO2 photocatalysts as it fulfilled the requirement properties to enhance the photocatalytic activity of TiO2 in the photoreduction process. Based on SEM analysis, the surface morphology of Al2O3-TiO2 catalyst exhibits well arranged aggregates with many small spherical particles. Meanwhile FTIR analysis, the presence of Al-O bonds in the TiO2 powder was successfully obtained as the peaks of 947.75 cm-1 fall in the general range of Al-O vibrations. Other than that, based on XRD pattern of Al2O3-TiO2 it revealed the existence of polymorphs anatase TiO2 which usually shows greatly superior in photoactivity of TiO2. Most importantly, based on BET analysis, the prepared Al2O3-TiO2 catalysts show a great crystal growth with 153.8599 m2/g specific surface area and 8.8 nm of pore size diameter. A nano size material leads to improvement in the electron hole pair separation and enhance the photoactivity of TiO2.